Sustainable surface modification of textile with Ag-doped TiO2/polysiloxane nanocomposite for antibacterial, UV protection, and flame retardant properties - Rashid, Mohammad Mamunur; Tomšič, Brigita; Simončič, Barbara; Jerman, Ivan; Štular, Danaja; Zorc, Matija (Wydawnictwo Politechniki Łódzkiej, 2022)
In this work, a cotton fabric with advanced photocatalytic and flame retardant properties was developed by using Ag-doped TiO2 in combination with 3-(trihydroxysilyl)propyl methyl phosphonate (TPMP) with a sustainable sol-gel/hydrothermal approach. Scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDS) were used to confirm the successful application of Ag-doped TiO2 and TPMP on the cotton fabric. The results of UPF, bacterial reduction against Escherichia coli and vertical flammability test showed that the creation of Ag-TiO2+TPMP nanocomposite on the surface of the fibres gave the cotton fabric superior antibacterial activity, very good UV protection and flame retardant activity.
Keywords: cotton fabrics; titanium dioxide (TiO2); Ag-doping; antibacterial activity; UV protection; flameretardancy; tkaniny bawełniane; dwutlenek tytanu; TiO2; Ag-doping; działanie antybakteryjne; ochrona UV; ognioodporność